Design and Implementation of Smart Parking System Using Location-Based Service and Gamification Based On Internet Of Things - Alam Nasyrah Muharram Nasution; Rendy Munadi; Sussi Sussi (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2021)
Information on the number of available parking slot capacity and trip routes to the destination parking area, and motivation in choosing a parking area location are parameters that can help two-wheeled vehicle users choose the right parking area location. The three parameters that determine the accuracy of selecting a parking area location are implemented in an Internet of Things (IoT) based smart parking system. This system can provide information about the maximum number of slot capacities and the number of available slot capacities at the parking area. Two-wheeled riders are given information about which route to take to the destination parking area by utilizing the Location-Based Service (LBS). These two features are then supported by applying the gamification method to motivate two-wheeled riders to choose the right parking area. The smart parking system is tested with considered Quality of Service (QoS) parameter and black box testing. The results of testing the smart parking system produce QoS performance on the Line of Sight (LOS) test, with an average delay is 71.66 ms, average jitter is 107.59 ms, and throughput is 23 kbps. Meanwhile, in the non-LOS test, the average delay is 132.88 ms, the average jitter is 200.84 ms, and the throughput is 12 kbps. Overall system performance obtained the percentage of reliability is 99.65 %, and availability is 99.65 %. In black-box testing, LBS and gamification methods can implement according to application requirements specifications.